Leader reputation: The role of mentoring, political skill, contextual learning, and adaptation - Blass, Fred R.; Ferris, Gerald R. (Human Resource Management, 2007)
AbstractLike organizations in other sectors, military settings can be appropriately characterized as political arenas.As such, political skill is critical for military leader effectiveness and leader reputation.This article proposes a conceptual model that articulates the roles of political skill, contextual learning, impression management, and adaptation in leader reputation development for military personnel aspiring to leadership positions. Political skill is shaped by mentoring and contextual learning experiences, which, in turn, affect the flexibility needed for making favorable impressions on others, adaptation, and fit. Implications of the proposed model for developing a more informed understanding of leader effectiveness and reputation in the military are discussed, as are directions for future research. ©2007 Wiley Periodicals, Inc.